2010
DOI: 10.1002/jcb.22704
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide phosphoribosyltransferase/sirtuin 1 pathway is involved in human immunodeficiency virus type 1 Tat‐mediated long terminal repeat transactivation

Abstract: Tat is a multifunctional transactivator encoded by human immunodeficiency virus type 1 (HIV-1). Tat transactivating activity is controlled by nicotinamide adenine nucleotide(+) (NAD(+))-dependent deacetylase sirtuin 1 (SIRT1). Nicotinamide phosphoribosyltransferase (Nampt) is a rate-limiting enzyme in the conversion of nicotinamide into NAD(+), which is crucial for SIRT1 activation. Thus, the effect of Nampt on Tat-regulated SIRT activity was studied in Hela-CD4-beta-gal (MAGI) cells. We demonstrated that Tat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 36 publications
1
15
0
1
Order By: Relevance
“…13 A major factor contributing to the requirement of AMPK to provide PKCemediated ischemic neuroprotection in our experiments may lie in the ability of AMPK to regulate Nampt and NAD levels. Ischemic preconditioning and resveratrol have been shown to enhance levels of Nampt, 33,34 which implicates Nampt as a major player in ischemic neuroprotection. Studies have shown that knockdown of Nampt increases susceptibility to cerebral ischemic infarct, while Nampt overexpression enhances neuronal survival after ischemic injury through AMPK activity.…”
Section: Discussionmentioning
confidence: 99%
“…13 A major factor contributing to the requirement of AMPK to provide PKCemediated ischemic neuroprotection in our experiments may lie in the ability of AMPK to regulate Nampt and NAD levels. Ischemic preconditioning and resveratrol have been shown to enhance levels of Nampt, 33,34 which implicates Nampt as a major player in ischemic neuroprotection. Studies have shown that knockdown of Nampt increases susceptibility to cerebral ischemic infarct, while Nampt overexpression enhances neuronal survival after ischemic injury through AMPK activity.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated that HIV-1 Tat protein is a substrate of SIRT1 for deacetylation and functional inhibition or knockdown of SIRT1 is known to enhance Tat’s ability to transactivate HIV-1 (Pinzone et al, 2013; Zhang et al, 2010; Zhang and Wu, 2009). By contrast, in SIRT1-null mouse cells, where there is no SIRT1 expression, Tat transactivation is defective but can be rescued by expression of SIRT1 (Pagans et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…All immunoblots were visualized using the Odyssey infrared imaging system (LI-COR Biosciences) according to the manufacturer's instructions. Densitometry was performed using Li-Cor Odyssey instrument software (Zhang et al, 2010).…”
Section: Immunoblottingmentioning
confidence: 99%